PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT RAM BKT - Sopiati, Sopiati; Astikawati, Yunita (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
PT RAM BKT (Berjaya Kalimantan Transport) is one of the strategic industries operating in the agricultural sector (agro-industry). This research aims to carry out an evaluation of the influence of the work environment on employee performance. The problem raised in this research is how the work environment affects employee performance at PT RAM BKT (Berjaya Kalimantan Transport). This research uses a quantitative approach, with data taken through distributing questionnaires to employees at PT RAM BKT (Berjaya Kalimantan Transport). The technical analysis used is regression using the SPSS version 26 application. The results of the research conclude that the work environment has an influence on overall employee performance. This condition shows that employee consistency in their work influences the way they work and produces good performance. In addition, a conducive work environment provides support for employees to improve their performance, so that they can provide optimal work results and complete tasks on time